Report of the Sensitisation Workshop on Rural Radio for Policy and Decision Makers in East and Southern Africa - Food and Agriculture Organization of the United Nations (Food and Agriculture Organization of the United Nations, 2006)
This workshop follows findings of two studies on training needs for rural radio in Africa (1999 and 2000) carried out by CIERRO and SADC CCD...